Positioning Control and Operational Evaluation of A One Mass Rotary System using NCTF Controller - Mohd Nor, Rozilawati; Md Rozali, Sahazati; Shin Horng, Chong (International Journal of Engineering and Technology, 2018)
A practical control scheme is proposed for a one mass rotary system. It was written to demonstrate the controller performance towards positioning and tracking control. For this system, the Nominal Characteristic Trajectory Following (NCTF) controller is proposed and improved. The objective of NCTF controller is to make the object motion to follow the NCT and ends at it origin. Generally, the NCTF controller consists of a Nominal Characteristic Trajectory (NCT) obtained from open loop response and Proportional Integral (PI) compensator. The CM-NCTF controller is proposed for evaluating the motion performance and compare with the conventional NCTF controller. For positioning control, both NCTF controllers demonstrate almost identical positioning performance. However, for tracking control, CM-NCTF controller demonstrates better tracking performance than the conventional NCTF controller with the smallest motion error presented. Besides, the robustness of the CM-NCTF controller to the variation load is examined.Â